Kajian Kriminologi terhadap Kekerasan yang Dilakukan oleh Perempuan di Kota Kupang - Agatha Novarilla Akong; Bhisa Vitus Wilhelmus; Rosalind Angel Fanggi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this study is to find out and analyze the criminological study of violence committed by women in Kupang City. This research is an empirical legal research, the sources and types of data in this study are primary data obtained from interviews at the Kupang City Police, Kupang Class II B Women's Correctional Institution and in the community and secondary data obtained from literature studies, then processed by checking, reconstructing, after which the material is regularly fixed so that it is easy to understand. From this study, the author can conclude that the factors that cause violence by women in Kupang City are classified into two, namely internal factors, namely prolonged stress and external factors, namely economic factors, environmental factors, and opportunity factors. Apart from that, the reaction of the people of Kupang City to violence committed by women in Kupang City consists of reactions in the form of rejection, understanding, and indifferent reactions from the community.